MODEL IMPLEMENTASI KURIKULUM DALAM MENINGKATKAN LIFE SKILL SISWA SDIT AT-TAUFIQ BOGOR - Arifian, Andri (Tawazun: Jurnal Pendidikan Islam, 2018)
Curriculum Implementation Model In Improving Student Life Skill of SDIT At Taufiq Bogor. Guided by Hasbi Indra, and Maemunah Sa'diyah. In this study the authors attempt to collect data and then analyze the implementation of the curriculum model in improving the life skill of SDIT At Taufiq students. The research focuses on analyzing curriculum implementation model, life skill contents in SDIT At Taufiq curriculum, life skill learning process at SDIT At Taufiq, and life skill curriculum implementation model at SDIT At Taufiq. This research is field research. The approach used is descriptive research, while the method used in this study is a case study (case study). And the techniques used in data collection is by in-depth interviews, observation and documentation studies.The results showed that life skills applied in SDIT At Taufiq are four, namely self-awareness, self-management, leadership and responsibility, and charity management. Life skill learning held at At Taufiq school is aligned with the vision of the school's mission of printing the Islamic generation. Life skill implementation model developed by learning by doing method and qudwah teacher in everyday in and out of class. Increased competence of learners can be seen from the independence of learners in everyday life. Problem solving skills in the daily life of learners independently is one form of success in life skill learning. So as to give a significant impact in forming individual students who are character, creative, independent and religious.